Relationship Between Self Care Management with Quality Of Live of Elderly Chronic Disease Management Program members at Grogol Sukoharjo Health Center - Putri Rahayu; Kartinah Kartinah (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Chronic disease management program (Prolanis) is a program that focuses on 2 diseases, namely hypertension and diabetes mellitus. Increased blood pressure exceeding 140 mmHg for diastole and above 90 mmHg for systole is hypertension. Although elevated blood sugar (glucose) levels in the body are a diabetic mellitus. Both diseases can attack anyone, especially the elderly. The elderly are very susceptible to disease due to decreased immunity and physical health.The disease can become complication that leads to death. With these complications, it's likely to disrupt the quality of life in the elderly. One effort to improve the quality of life of population, including the elderly, requires effective and efficient management in the form of self-care behavior management. The purpose of this study is to ascertain how elderly Prolanis members' quality of life and self care management relate to one another. This research uses cross-sectional methodology and is quantitative in nature. From May to June 2024, this study was carried out at the Grogol Sukoharjo Community Health Center. There were 288 elderly Prolanis members at the Grogol Sukoharjo Community Health Center who made up the study's population. Purposive sampling was the method utilized in the sampling process, providing an 81-person sample. The WHOQOL-BREF and the chronic disease self-care management questionnaire were utilized for data collection. Chi-square test used in bivariate analysis of research data. The statistical test obtained p value (0.001) <a value (0.05). So, it can be concluded that there is relationship between self care management and quality of life (p = 0.001). From this, self care management can affect the quality of life the elderly. Therefore, the community health center can optimize health education services regarding self care management to all Prolanis members so that it's expected to reduce disease complications. Keywords: Cronic Diseases, Elderlyl, Quality of Life, Self Care Management